Parkinson’s Disease and the Gut: Future Perspectives for Early Diagnosis - Harsanyiova, Jana; Buday, Tomas; Kralova Trancikova, Alzbeta (Frontiers in Neuroscience, 2020)
Parkinson’s disease (PD) is a neurodegenerative disease characterized by progressive degeneration of dopaminergic neurons, and at the cellular level by the formation of Lewy bodies in the central nervous system (CNS). However, the onset of the disease is believed to be localized to peripheral organs, particularly the gastrointestinal tract (GIT) and the olfactory bulb sooner before neuropathological changes occur in the CNS. Patients already in the pre-motor stage of PD suffer from various digestive problems and/or due to significant changes in the composition of the intestinal microbiome in this early stage of the disease. Detailed analyses of patient biopsies and autopsies as well as animal models of neuropathological changes characteristic of PD provided important information on the pathology or treatment of PD symptoms. However, presently is not clarified (i) the specific tissue in the GIT where the pathological processes associated with PD is initiated; (ii) the mechanism by which these processes are disseminated to the CNS or other tissues within the GIT; and (iii) which neuropathological changes could also serve as a reliable diagnostic marker of the premotor stages of PD, or (iv) which type of GIT tissue would be the most appropriate choice for routine examination of patient biopsies.